Performance of durum wheat lines for quality and rust resistance - Oak, M D; Patil, R M; Bankar, D N; Bagwan, J H; Bipinraj, A L; Tamhankar, S A; Honrao, B K; Misra, S C (Journal of Cereal Research, 2011)
Stem rust (Puccinia graminis Pers. f. sp. tritici) and leaf rust (Puccinia triticina Rob. ex. Desm.) are the major constraints in wheat production in the peninsular zone. A number of wheat varieties cultivated in the past, became susceptible to rust, after a few years of cultivation. Traditionally wheat improvement aims at three major aspects viz. grain yield, disease resistance and quality. The effect of disease on yield and its components in general has been adequately studied (Mundy 1973, Knott 1989). However, there is still ample scope to study its interaction with physiology and quality in wheat. Allard (1960) suggested that early generation selection should be restricted to highly heritable traits such as disease resistance and plant height and that the traits showing low heritability should be evaluated only in those lines that survive this screening. Such a pedigree breeding system involves the retention of lines of unknown grain yield potential until a degree of homozygosity is attained (F5 or F6). In view of the severeness of the rust diseases, as well as the necessity to improve the quality of wheat, an attempt has been made to combine rust resistance and quality attributes in durum wheat.